2009
DOI: 10.4161/cbt.8.1.7209
|View full text |Cite
|
Sign up to set email alerts
|

PIK3CA amplification associates with resistance to chemotherapy in ovarian cancer patients

Abstract: PI3K/AKT signalling pathway controls important cellular processes such as the cell proliferation and apoptosis. PIK3CA gene encoding a catalytic subunit of the PI3K is mutated and/or amplified in various neoplasms, including ovarian cancer. We aimed to evaluate PIK3CA alterations and their clinical importance in ovarian cancer patients. Molecular analysis was performed on 117 ovarian carcinomas with the use of qPCR, SSCP and sequencing. In a group of 98 patients with complete clinical data, 62 patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 29 publications
1
54
0
1
Order By: Relevance
“…Other methods used included immunocytochemistry and real-time quantitative polymerase chain reaction. There was only 1 prospective study [11], and the rest were all retrospective studies [10,12,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other methods used included immunocytochemistry and real-time quantitative polymerase chain reaction. There was only 1 prospective study [11], and the rest were all retrospective studies [10,12,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There was no heterogeneity between studies. However, there was only one study that reported an association between PI3K expression and PFS with multivariate analysis [34].…”
Section: The Relationship Between Biomarker Status and Pfsmentioning
confidence: 99%
“…These tumors commonly exhibit activation of the PI3K/Akt pathway via PIK3CA mutation (6), loss of PTEN, PTEN mutation (7), or increased expression of mir-214 targeting PTEN (8). Current therapeutic strategies for ovarian cancer involve platinum-or taxane-based chemotherapeutics, which are typically effective initially, but often fail because of acquired resistance attributed to diverse molecular causes, one of which is increased activity of the PI3K pathway (9)(10)(11). These findings indicate that ovarian cancer patients are likely to benefit from the development of PI3K pathway inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Pathway activation through PIK3CA can occur through either amplification or activating mutation of the catalytic subunit. Mutations of PIK3CA are typically associated with endometrioid and clear cell subtypes and are associated with lower tumor stage and grade (Campbell et al 2004, Kolasa et al 2009, Willner et al 2007. Amplifications, on the other hand, have been detected in all histological subtypes, though there was an association with poorer differentiation.…”
Section: Pik3ca and Akt2mentioning
confidence: 99%
“…Amplifications, on the other hand, have been detected in all histological subtypes, though there was an association with poorer differentiation. PIK3CA amplification has been reported in 13-24% of ovarian carcinomas and is associated with increased expression of phosphorylated AKT indicating that amplification results in increased activation of the pathway (Campbell et al 2004, Kolasa et al 2009, Nakayama et al 2006b, Willner et al 2007, Woenckhaus et al 2007. Clinical data is lacking in the majority of these studies and the prognostic role of AKT and mTOR in ovarian cancer is unclear.…”
Section: Pik3ca and Akt2mentioning
confidence: 99%